KUALITAS AIR DAN DINAMIKA FITOPLANKTON DI PERAIRAN PULAU HARAPAN - Soetrisno, Yudhi (Jurnal Hidrosfir Indonesia, 2008)
This research was conducted to known water quality and phytoplankton dynamics in the coastal of Harapan island. The research reveal that during the period of research the coastal water of Harapan island was an olygotrophic withphytoplankton density about 654,7-1.745 cells/ml. The phytoplankton community in November was dominated by Thalassionema sp. (303.64 cells/ml); in 10 December was by Pseudonitzchia sp (117,7 cells/ml); in 7 January was byChaetoceros sp (218 cells/ml), in 28 January was by Trichodesmium sp; (727,3cells/ml) and in 22 April was by Chaetoceros sp. (775.8 cells/ml). It have to payattention to the dominating phytoplankton community by Pseudonitzchia sp andTrichodesmium sp due to their bloom will create negative impact to otherorganisms and ecosystem stability.